Microfluidic Surface Plasmon Resonance Sensors: From Principles to Point-of-Care Applications - Da-Shin Wang; Shih-Kang Fan (Sensors, 2016)
Surface plasmon resonance (SPR) is a label-free, highly-sensitive, and real-time sensing technique. Conventional SPR sensors, which involve a planar thin gold film, have been widely exploited in biosensing; various miniaturized formats have been devised for portability purposes. Another type of SPR sensor which utilizes localized SPR (LSPR), is based on metal nanostructures with surface plasmon modes at the structural interface. The resonance condition is sensitive to the refractive index change of the local medium. The principles of these two types of SPR sensors are reviewed and their integration with microfluidic platforms is described. Further applications of microfluidic SPR sensors to point-of-care (POC) diagnostics are discussed.